Microwave Pyrolysis of Water hyacinth for Biochar Production Using Taguchi Method - I. Abd, Noor; Mohammed Al-Mayah, Ameel; K. Muallah, Shatha (International Journal of Engineering and Technology, 2018)
The manuscript should contain an abstract. The abstract should be self-contained and citation-free and should not exceed 200 words. The abstract should state the purpose, approach, results and conclusions of the work. The author should assume that the reader has some knowledge of the subject but has not read the paper. Thus, the abstract should be intelligible and complete in it-self (no numerical references); it should not cite figures, tables, or sections of the paper. The abstract should be written using third person instead of first perso The fast microwave assisted pyrolysis (FMWAP) of water hyacinth (WH) for biochar production is investigated. Taguchi’s method was used to optimize FMWAP parameters. The effects of microwave power, temperature, microwave absorber (activated carbon) ratio, and biomass particle size on biochar yield as the response for the process, were studied. The maximum yield was achieved using the optimized conditions of microwave power-994 W; temperature-300°C; microwave absorber ratio-0.25; and biomass particle size-0.0315 mm. The reaction time was kept constant at 2 min. The analysis of Signal to Noise ratio (S/N) and variance (ANOVA) were used to identify the effect and the significance of the process parameters on biochar yield. The final results show the significance of all process parameters on biochar yield. The order of significance of these parameters are: microwave power > temperature > microwave absorber > biomass particle size. The produced biochar was analyzed by scanning electron microscopy (SEM) and Energy Dispersive X-Ray Analyzer (EDX). The WH biochar has macroporous and microporous structure and amorphous in nature with some mineral oxides attached to the surface.